2017
DOI: 10.5483/bmbrep.2017.50.4.029
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical targets play an important role in microRNA stability control mechanisms

Abstract: MicroRNAs (miRNAs) regulate gene expression by guiding the Argonaute (Ago)-containing RNA-induced silencing complex (RISC) to specific target mRNA molecules. It is well established that miRNAs are stabilized by Ago proteins, but the molecular features that trigger miRNA destabilization from Ago proteins remain largely unknown. To explore the molecular mechanisms of how targets affect the stability of miRNAs in human Ago (hAgo) proteins, we employed an in vitro system that consisted of a minimal hAgo2-RISC in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These results indicated that LINC00968 could bind to hsa-miR -423-5p. It is known that miRNAs play a role in RNA silencing by forming an RNA-induced silencing complex (RISC), such as Ago protein family that binds to and stabilize mature miRNAs [23]. Therefore, we determined whether LINC00968 and hsa-miR-423-5p formed RISC together.…”
Section: Linc00968 Binds To Hsa-mir-423-5pmentioning
confidence: 99%
“…These results indicated that LINC00968 could bind to hsa-miR -423-5p. It is known that miRNAs play a role in RNA silencing by forming an RNA-induced silencing complex (RISC), such as Ago protein family that binds to and stabilize mature miRNAs [23]. Therefore, we determined whether LINC00968 and hsa-miR-423-5p formed RISC together.…”
Section: Linc00968 Binds To Hsa-mir-423-5pmentioning
confidence: 99%
“…Unexpectedly, some miRNAs are destabilized by specific interactions with mRNAs [68,69]. These transcripts contain sequences that have a near-perfect match with miRNAs and contain centered mismatches.…”
Section: Introductionmentioning
confidence: 99%